Environmental risk assessment for sustainable industrial urban development: The case of northern industrial zone of Pavlodar, Kazakhstan - Zhanat Shomanova; Yuriy Nossenko; Meruert Yerkibayeva; Dinara Yessimova; Aikun Kuspanova; Ardak Aldasheva; Kulyash Kaimuldinova; Ruslan Safarov (PLoS ONE, 2025)
This study assesses heavy metal (HM) contamination in soils of an urban industrial zone using statistical and spatial analysis methods. Concentrations of 12 key HMs, including Zn, Pb, Cu, and Ni, were measured using X-ray fluorescence (XRF), with values exceeding background levels several times in certain areas. Pollution indices such as the Pollution Load Index (PLI) and Total Pollution Indicator (Zc) revealed moderate to high contamination levels, with PLI values ranging from 1.05 to 3.38 and Zc values between 0.67 and 51.34. Health risk assessments indicated that the hazard quotients (HQ) exceeded safe thresholds in hotspots, highlighting potential risks. Spatial distribution maps identified industrial activities as the primary source of contamination. Specifically, according to the PLI, approximately 93.757% of the studied area is classified as moderately contaminated, while 0.702% is considered significantly contaminated. These findings provide a baseline for monitoring and mitigating soil pollution in industrial regions while offering insights for sustainable land management.